Degradation and Aggradation Parabolic Model of Dengkeng Riverbed - Fauziyah, Syifa; Ihsan, Cahyono; Sobriyah, Sobriyah (Institut Teknologi Sepuluh Nopember, 2017)
The stability of riverbed became an important part in the river. Basically, the stability would be maintained if the grains of sediment was not moving (transported). Riverbeds that were disrupted because of carried details (degradation) or stacked granules (aggradation) in certain parts of the river caused the structure to be damaged. Degradation and aggradation along the river road at a certain time would be figured out in this study, so that it could assist in making treatment recommendations layer riverbed. The case study was conducted on Dengkeng River along the 8 km segment Karangjoho-Jetis which was a fixed flow (quasi-steady) sub critical Froude number <0.6. Bottom sediment sample material with a grain diameter variation D35, D50, D65, and d90 in grain size analysis was used for the calculation. The process of degradation and aggradation riverbed sediment discharge was known by calculation using the method of Meyer-Petter & Muller. Parabolic model analysis with the help of MS Excel was used to calculate the degradation and aggradation happened. At the time of running, graph illustrating the comparison between degradation and aggrades with a segment length of the river at a certain time was seen. The graph showed the longer segment of the river, degradation and aggradation would less.